Fate of the Atlantic Meridional Overturning Circulation: Strong decline under continued warming and Greenland melting. Issue 23 (13th December 2016) - Bakker, P.; Schmittner, A.; Lenaerts, J. T. M.; Abe‐Ouchi, A.; Bi, D.; van den Broeke, M. R.; Chan, W.‐L.; Hu, A.; Beadling, R. L.; Marsland, S. J.; Mernild, S. H.; Saenko, O. A.; et al.
Abstract: The most recent Intergovernmental Panel on Climate Change assessment report concludes that the Atlantic Meridional Overturning Circulation (AMOC) could weaken substantially but is very unlikely to collapse in the 21st century. However, the assessment largely neglected Greenland Ice Sheet (GrIS) mass loss, lacked a comprehensive uncertainty analysis, and was limited to the 21st century. Here in a community effort, improved estimates of GrIS mass loss are included in multicentennial projections using eight state‐of‐the‐science climate models, and an AMOC emulator is used to provide a probabilistic uncertainty assessment. We find that GrIS melting affects AMOC projections, even though it is of secondary importance. By years 2090–2100, the AMOC weakens by 18% [−3%, −34%; 90% probability] in an intermediate greenhouse‐gas mitigation scenario and by 37% [−15%, −65%] under continued high emissions. Afterward, it stabilizes in the former but continues to decline in the latter to −74% [+4%, −100%] by 2290–2300, with a 44% likelihood of an AMOC collapse. This result suggests that an AMOC collapse can be avoided by CO2 mitigation. Key Points: This is the first model intercomparison concerning climate change including Greenland melt and a probabilistic uncertainty assessment Impact of Greenland melt on future overturning circulation is small but nonnegligible especially for high‐end global warming scenarios Likelihood of a full overturning collapse remains exceptionally small if global warming is limited to less than 5 K